(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
The implementation of high-temperature synthesis processes through solar energy concentration is considered a highly efficient and environmentally friendly method. Proper selection of the optical–energetic parameters of the Large Solar Furnace (LSF) system prevents excessive overheating of the material and enables the production of high-temperature superconducting (HTS) materials with the required electrophysical properties [1]. Through the modeling process, it becomes possible to account for and minimize radiation losses, reduce experimental costs, and enhance the efficiency of synthesis [2].